Core skills appraisal project: assessing and preparing adults to return to learning - Eleanor Rafferty (Scottish Journal of Residential Child Care)
With the introduction in 2003 of the Scottish Social Services Council's (SSSC) requirement to register, approximately 3000 residential child care (RCC) staff were faced with the prospect of returning to formal education. While residential child care workers welcomed the opportunity to improve the status of their field within the social services sector, many people had joined the sector at a time when no qualifications were required.